Kewirausahaan dalam Perspektif Syari’ah - Miftachul Jannah; Nur Lailatul Musyafaah; Nur Ismi Febrianti (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2018)
This article discusses entrepreneurship from the perspective of sharia. This research is the result of a literature review, by collecting data through literature books, journals, and the internet. The collected data were analyzed descriptively. The results of the study concluded that Islam advocates entrepreneurship as a person's endeavor to meet their needs independently. In entrepreneurship, a person is required to pay attention to business ethics in Islam, namely being honest, trustworthy, tabligh and fathanah. By doing entrepreneurship according to the rules and principles of Islamic economics, it is hoped that someone will get blessings in the world and the hereafter. Because of that, several taboos should be avoided by a Muslim entrepreneur, namely maysir, immorality, gharar, haram, ihtikar, and danger. In entrepreneurship, a Muslim must be based on a moral foundation, Islamic management, a high work ethic and have an attitude of leadership, responsibility, and have a strong entrepreneurial spirit.